HUBUNGAN ANTARA INFEKSI SALURAN KEMIH KOMPLEKS DENGAN GAGAL TUMBUH - , PUJI ASTUTI, dr. Mei Neni Sitaresmi, PhD, Sp.AK. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The velocity of urine flow can be a protective factor towards urinary tract infection (UTI). In patients with anatomical malformation that causes obstruction in urine flow, UTI can be happen frequently. Recurrent UTI can cause a decrease appetite, decrease the absorption of nutrition, and increase basal metabolic rate thus increasing the energy requirement. This factor will be a risk factor for growth failure. Aim: To identify whether UTI is a risk factor for growth failure in children with complicated UTI. Method: This study used a retrospective cohort design with 42 children first diagnosed with simple and complicated UTI from January 1st 2010 to August 31st 2012 in outpatient clinic and childrenâs ward of Sardjito General Hospital. The data of height and age at the time of diagnosis were collected from medical records. Other data of present height were collected by home visits. The height velocity (cm/year) were calculated subtracting the present height with the height at the time of diagnosis, divided by time between measurements. Growth failure was defined by the growth velocity below normal range (< 25th percentile of the growth velocity curve corrected by age and sex). Statistic analysis using bivariate analysis with fischer exact test has done to find of the relation. Results: Growth failure was found in 10 out of 21 children with complicated UTI (47.6%) and 4 out of 21 children with simple UTI (19.0%) (p=0,050, RR 3,864, CI 95% 0.967-15.443). Conclusion: Complicated UTI was not risk factor to be growth failure. Although not statistically significant in our study, children with complicated UTI have a trend towards growth failure.